Potent Restriction of Sexual Zika Virus Infection by the Lipid Fraction of Extracellular Vesicles in Semen - Wang, Ruofan; Gornalusse, Germán G.; Kim, Yeseul; Pandey, Urvashi; Hladik, Florian; Vojtech, Lucia (Frontiers in Microbiology, 2020)
Sexual Zika virus (ZIKV) transmission from men to women occurs less frequently than the often-detected high viral loads in semen would suggest, but worries that this transmission route predisposes to fetal damage in pregnant women remain. To better understand sexual ZIKV pathogenesis, we studied the permissiveness of the human female genital tract to infection and the effect of semen on this process. ZIKV replicates in vaginal tissues and primary epithelial cells from the vagina, ectocervix and endocervix and induces an innate immune response, but also continues to replicate without cytopathic effect. Infection of genital cells and tissues is strongly inhibited by extracellular vesicles (EV) in semen at physiological vesicle-to-virus ratios. Liposomes with the same composition as semen EVs also impair infection, indicating that the EV’s lipid fraction, rather than their protein or RNA cargo, is responsible for this anti-viral effect. Thus, EVs in semen potently restrict ZIKV transmission, but the virus propagates well once infection in the recipient mucosa has been established.